NECESIDAD DE REGULAR EL ART. 272 DEL CÓDIGO ORGÁNICO INTEGRAL PENAL, SEÑALANDO EN EL DELITO DE FRAUDE PROCESAL EXCEPCIONES DE RESPONSABILIDAD PENAL POR LA EXISTENCIA DE LOS NEXOS DE PARENTESCO - Pogo Sánchez, Jony Patricio (2016)
The second paragraph of Article 272 of the Code of Criminal Integral in relevant part as regulates matters relating to procedural fraud as a separate offense that is punishable expresses one to three years who know the criminal conduct of a person or persons, provide them housing or hiding or provide them with the means to take advantage of the effects of the crime, or encourage them by hiding the instruments or elements of the offense, this being a crime against judicial activity, because it provides or helps to conceal the actions of authors or accomplices of a crime. However, procedural fraud as a new legal form, as to concealment noted in the previous legislation, represents the same legal spirit, does not change its nature. In the previous regulation under the heading of those responsible for the infringements, exemptions cover-up, among which comprised the relative spouses, their parents, children, siblings or affinity up to the second degree is established; instituting with the exemption of criminal responsibility, protection indisputable benefit of the most basic and elementary family ties; is protected as it could not be otherwise, the cell of society, in response to the natural reaction between parents and children and vice versa, seeking where possible to establish some degree of protection to self-protection would say between the closest members the family; even a religious order mandate says we should honor father and mother. 5 The basis for this exception is the presumption that the activity of procedural fraud is selfless and emotional when it comes to parents, children, siblings or spouse, it is therefore very human except as otherwise would be blameworthy not hide a being intimate or underlying elements to frame him is against the affective level whose family. It should be noted that with respect to procedural fraud, it is not against such figure; but I believe that there is a gap in the Code of Integral Criminal, by failing to establish as exceptions to criminal liability, the existence of kinship ties already indicated between the offender and who commits a crime against judicial activity in order to induce mislead the judge, after the execution of a criminal offense, under the terms established by the second paragraph of Article 272 of the new penal regulatory body; vacuum that must be overcome for the benefit of family harmony.